CLIL METHODOLOGY OF TEACHING ENGLISH IN THE FIELD OF PROFESSIONAL COMMUNICATION (Web of Teachers: Inderscience Research, 2023)
In this article, several methods of effective teaching of English for special purposes and some of the innovative educational technologies used in language and its learning are highlighted.